HEALTHY LIFESTYLE OF STUDENTS: PROBLEMS AND THEIR SOLUTIONS (Pedagogy of Higher and Secondary Education, 2007)
In article the theoretical analysis of researches on a problem of a healthy way of life of students is given; are given own sociological research; ways of the decision of a problem of formation of a healthy way of life of students are shown.